If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2c + 22 = 7c + -10 Reorder the terms: 22 + 2c = 7c + -10 Reorder the terms: 22 + 2c = -10 + 7c Solving 22 + 2c = -10 + 7c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-7c' to each side of the equation. 22 + 2c + -7c = -10 + 7c + -7c Combine like terms: 2c + -7c = -5c 22 + -5c = -10 + 7c + -7c Combine like terms: 7c + -7c = 0 22 + -5c = -10 + 0 22 + -5c = -10 Add '-22' to each side of the equation. 22 + -22 + -5c = -10 + -22 Combine like terms: 22 + -22 = 0 0 + -5c = -10 + -22 -5c = -10 + -22 Combine like terms: -10 + -22 = -32 -5c = -32 Divide each side by '-5'. c = 6.4 Simplifying c = 6.4
| 3(x+4)+8=-10 | | 2(x-5)-4-5x+1=0 | | x=.5(3x-13) | | 2x+y-76=0 | | x=.5(2x-10-3) | | 291+x=360 | | v+2.59=4.69 | | 2y-2+4y-32+y+8=360 | | x-61=12.5 | | 12Y+17=161 | | X^2-18x+81=2001 | | 27.48+x=3.29x | | -5x-6+4x=12 | | 3x-6(-5x+17)=162 | | -3y-1+2y=-1 | | (4x-40)/2=(2x-90)x4 | | (4x-40)/2=(2x-90)4 | | -1/8(8y-72) | | (4x-40)/2=(2x-90)*4 | | v-2.14=4.4 | | w*8+4=13 | | Y=x^2+9x-112 | | 1/3y-1/3=-6 | | 5x-12+5=-3 | | 1x-2x/5=3 | | 4x+75=9x+95 | | 4(3x-1)-5(3x-2)=2(x+2)-5x | | 2(2x)-3(x+5)=-13 | | 12-4*0+1=0 | | -10.2=-3.4c | | 5(x/5-3)=30 | | 5x+27-2x=0 |